Ni(i)–Ni(iii) cycle in Buchwald–Hartwig amination of aryl bromide mediated by NHC-ligated Ni(i) complexes. Issue 8 (25th February 2019) - Inatomi, Takahiro; Fukahori, Yukino; Yamada, Yuji; Ishikawa, Ryuta; Kanegawa, Shinji; Koga, Yuji; Matsubara, Kouki
Abstract : NHC-ligated Ni(i ) intermediates in Buchwald–Hartwig amination of aryl halides were isolated and determined. The presence of a Ni(iii ) intermediate was also indicated at low temperature. Abstract : Intermediate amide complexes of NHC-ligated monovalent nickel in Buchwald–Hartwig amination of aryl halides were isolated and structurally characterized. The amide complexes reacted with aryl bromide to form a cross-coupling product. Low-temperature observation of the oxidative addition product of the Ni(i ) amide complex with aryl bromide indicated the presence of a Ni(iii ) intermediate. The results showed that a well-defined mononuclear NHC–Ni(i ) complex can act as a key intermediate in homogeneous catalysis.